2019
DOI: 10.30685/tujom.v4i3.61
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Factors Affecting Consumers’ Intention Toward Purchasing Imitation Jewelry: An Extension of Theory of Planned Behavior

Abstract: This study examines the influencing factors those affect Bangladeshi consumers’ attitude and intention towards purchasing imitation jewelry through the conceptual extension of a theoretical model known as Theory of Planned Behavior (TPB). The authors proposed an Extended Theory of Planned Behavior (ETPB), consisting of seven factors: attitude, subjective norms, perceived behavioral control, product knowledge, value consciousness, fashion innovativeness and behavioral intention. Structural Equation Modeling (SE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
(77 reference statements)
1
1
0
Order By: Relevance
“…Moreover, the results demonstrated that perceived behavioral control significantly influenced consumers’ intention to purchase a face mask. This suggests that consistent with previous research [ 6 ], consumers will invest effort to obtain the desired product despite factors, such as availability, that make it difficult. Ajzen’s [ 19 ] suggestion that perceived behavioral control should be measured using the same expectancy value model as attitude and subjective norm was useful, because it helped illuminate which factors influenced the perception of control.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Moreover, the results demonstrated that perceived behavioral control significantly influenced consumers’ intention to purchase a face mask. This suggests that consistent with previous research [ 6 ], consumers will invest effort to obtain the desired product despite factors, such as availability, that make it difficult. Ajzen’s [ 19 ] suggestion that perceived behavioral control should be measured using the same expectancy value model as attitude and subjective norm was useful, because it helped illuminate which factors influenced the perception of control.…”
Section: Discussionsupporting
confidence: 84%
“…Asian countries’ experience following the SARS epidemic suggests that consumers will need to be prepared to make decisions about the purchase of PPE, such as face masks, for the foreseeable future [ 5 ]. Previous research has demonstrated the relation between attitude and purchase intention [ 6 ]. For example, in a study on Pakistanis’ face mask attitudes and purchase intentions, attitudes toward face masks were found to have a positive and significant effect on purchase intention [ 7 ].…”
Section: Introductionmentioning
confidence: 99%